Enhanced internal ionic interaction of MFS efflux pump MdfA contributes to its elevated antibiotic export. Issue 1 (13th December 2022) - Li, Ying; Ge, Xizhen
Abstract : Enhanced internal ionic interaction of MdfA elevated the antibiotic resistance level of E. coli . Abstract : Infections caused by Gram-negative pathogens are difficult to manage due to their antibiotic resistance. Efflux pumps, which transport intracellular toxins out of the cytoplasm, play an important role in the detoxification of bacteria when treated with antibiotics. The major facilitator superfamily (MFS) is a kind of widely distributed efflux pumps and can actively export clinically important antibiotics such as ciprofloxacin, while the role of internal ionic interactions in regulating drug export remains poorly understood. Herein we used a representative MFS efflux pump MdfA to investigate the impact of internal ionic interactions on the antibiotic resistance of E. coli . First, we identified the internal salt bridges of MdfA and searched their natural variants across all the sequenced E. coli isolates. By constructing these variants, we discovered that extending the salt bridge on the cytoplasmic side (E136D) conferred an elevated antibiotic resistance level of E. coli, and the level was further enhanced by combining it with an artificial mutation K346R. By analyzing the trajectories of MdfA's variants in molecular dynamics (MD) simulations, we revealed that ionic interaction strengths on the two sides were proportionally enhanced, while the protein flexibility was not affected. Moreover, enhanced interactions resulted in a larger surface for MdfA's protonation, suggesting a higher possibility for its activation. Collectively, our data revealed the importance of internal interactions on the drug export of MdfA, offering insights for the development of novel inhibitors against MFS efflux pumps.